Nuclear Energy - Poudel, Parashu Ram (Himalayan Physics, 2015)
Nuclear energy is the latest energy source to be used on a large scale. It has tremendous potentiality to meet the growing demand of energy without degrading the environment. Presently the nuclear fission of some heavy elements of the periodic table produces the vast majority of nuclear energy in the direct service of humankind. So nuclear energy produced by nuclear fission and its impacts are the main focus of this article. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 51-58